Digital Payment on Financial Transactions Towards Economic Growth in South East Asia Emergent Countries - Wibowo, Martino; Mubarok, Faizul; Rahman, Saif-Ur (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
Dear Editor-in-Chief, I am pleased to submit my manuscript titled